Предмет: Алгебра,
автор: sanektolkachev
Решите с помощью формулы приведения
tg(2п-x)=-tg x
Ответы
Автор ответа:
0
1)вариант решения:
tg(2π-x)=tg(-x)=-tg(x);
2)вариант решения:
tg(2π-x)=(tg2π-tgx)/(1+tg2π·tgx);⇒tg2π=0;
tg(2π-x)=-tgx/1=-tgx;
tg(2π-x)=tg(-x)=-tg(x);
2)вариант решения:
tg(2π-x)=(tg2π-tgx)/(1+tg2π·tgx);⇒tg2π=0;
tg(2π-x)=-tgx/1=-tgx;
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Психология,
автор: marinayusupova2000
Предмет: Биология,
автор: sashavasileva1